2007
DOI: 10.1017/s1463423607000369
|View full text |Cite
|
Sign up to set email alerts
|

Understanding family, social and health experience patterns in British Bangladeshi families: are people as diverse as they seem?

Abstract: Aim: An exploratory study of the Cardiff Bangladeshi community in a primary care setting, prior to the development of culturally appropriate diabetes health education. Background: British Bangladeshis are one of the most economically deprived communities in Britain, with high morbidity and mortality rates from chronic illness. Access and use of their services is perceived by Primary Health Care Teams (PHCTs) to be difficult, due to communication and cultural barriers. Methods: One-to-one taperecorded interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 15 publications
2
10
0
Order By: Relevance
“…In contrast, a study of twelve Bangladeshi patients found that family interpreters were preferred because of the benefits of shared understanding and privacy (Rhodes & Nocon 2003). This may, however, cause difficulties in arranging appointments if a family member, usually a man, is expected to be available for clinic visits with the patient (Hawthorne et al . 2007).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, a study of twelve Bangladeshi patients found that family interpreters were preferred because of the benefits of shared understanding and privacy (Rhodes & Nocon 2003). This may, however, cause difficulties in arranging appointments if a family member, usually a man, is expected to be available for clinic visits with the patient (Hawthorne et al . 2007).…”
Section: Resultsmentioning
confidence: 99%
“…There is broader evidence that families frequently serve as informal interpreting services in South Asian families (Brooks et al. 2000, Rhodes & Nocon 2003), so act as important intermediaries in self‐management behaviour; this may be particularly the case for elderly patients (Hawthorne et al. 2007).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Members of the Bangladeshi community (Hawthorne et al, 2007) may differ from each other in important respects: length of time living in high-income countries and in Bangladesh; whether English-or Bangladesh-educated; degree of fluency in reading, writing and speaking English; preference for traditional or Westernized lifestyles; religion; and so on.…”
Section: Bme Health Researchmentioning
confidence: 99%